Ethnography and the Roman Digressions of Ammianus Marcellinus - Creer, Tyler (Histos, 2020)
This article examines the content of Ammianus Marcellinus’ Roman digressions, the form and intent of which have been a consistent subject of debate for scholars, from the perspective of ethnographic writing. It highlights Ammianus’ comparison of the Romans of his day with those of the idealised past, as well as his unusual portrayal of the inhabitants of Rome as similar to the barbarian peoples described elsewhere in the Res Gestae. These aspects of Ammianus’ portrayal of the Romans, it is argued, exemplify the changing nature of Roman identity in Late Antiquity and suggest that at least part of the reason Ammianus wrote the digressions was to articulate an idealised conception of Romanness.